2022
DOI: 10.3390/jpm12030425
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Attitudes and Experiences with Pharmacogenomic Testing among Patients and the General Public: Implications for Patient Counseling

Abstract: The use of pharmacogenomic (PGx) tests is increasing, but there are not standard approaches to counseling patients on their implications or results. To inform approaches for patient counseling, we conducted a scoping review of published literature on patient experiences with PGx testing and performed a thematic analysis of qualitative and quantitative reports. A structured scoping review was conducted using Joanna Briggs Institute guidance. The search identified 37 articles (involving n = 6252 participants) pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 66 publications
1
15
0
Order By: Relevance
“…Most respondents agreed or strongly agreed that they wanted to learn more about pharmacogenetic testing, were curious about how their genetic code would affect their response to medications, and that pharmacogenetic testing could help their doctor with medication choice. This is consistent with the findings in other patient populations (Trinidad et al, 2015;Allen et al, 2022). Our data also indicated that patient testing expectations could be a potential barrier to patient acceptance of pharmacogenetic test results.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Most respondents agreed or strongly agreed that they wanted to learn more about pharmacogenetic testing, were curious about how their genetic code would affect their response to medications, and that pharmacogenetic testing could help their doctor with medication choice. This is consistent with the findings in other patient populations (Trinidad et al, 2015;Allen et al, 2022). Our data also indicated that patient testing expectations could be a potential barrier to patient acceptance of pharmacogenetic test results.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have evaluated various patient populations for their knowledge, attitudes, and perceptions towards pharmacogenetic testing (Rogausch et al, 2006;Zhang et al, 2014;Lachance et al, 2015;Chapdelaine et al, 2021;Kastrinos et al, 2021;Allen et al, 2022;Martin et al, 2022). However, there has been limited evaluation of the views of medically underserved populations.…”
Section: Introductionmentioning
confidence: 99%
“…This is the first systematic review to explicitly explore HCPs' and consumers' knowledge, attitudes, perspectives, and education needs for PGx in adult oncology care. Previous reviews included studies reporting on PGx across different specialities 15,42 . Our discipline‐specific approach allows identification for actionable change and advancement of PGx in oncology with greater precision.…”
Section: Discussionmentioning
confidence: 99%
“…Early implementation efforts of PGx testing largely relied on institutional support and external funding mechanisms to cover the costs due to the limited insurance coverage and reimbursement of PGx testing [ 18 , 38 , 39 ]. The cost of testing has been repeatedly identified as a major barrier for expansion and large-scale clinical adoption [ 13 , 40 , 41 , 42 ]. Therefore, having a better understanding of the public’s expectations and perspectives on the cost of PGx testing and the willingness-to-pay is an essential step in addressing the financial infrastructure of widespread PGx adoption.…”
Section: Discussionmentioning
confidence: 99%